La “clause auteur” : l’écrivain, l’ethos et le discours littéraire - Melliandro Mendes Gallinari (Argumentation et Analyse du Discours, 2009)
This essay develops a reflection on the question of authorship, more specifically on the various conceptions of authorship and its places of production, by investigating literary discourse, but also other kinds of social discourses. The term “author” is here understood as the result of an agreement between social subjects, namely as a convention endlessly varying according to historical moments and institutional spaces. In order to develop this point of view, we will draw on central categories of discourse analysis like communication contract or ethos.  We show how literary discourse constructs a peculiar “authorial ethos”  not to be confused with the production of authorial images in other frameworks like the media or literary criticism. Eventually, we question the modern and spectacular construction of the celebrity-author in its problematic relation to the authorial ethos and to the reading of the text.